Employees' Perception Of Organizational Climate In Shangri-La Hotels And Resorts In Singapore And Its Relationship Towards The Turnover Intention Of Its Employees - Yeat, Nai Shin (2009)
The main objective of this study is to explore the employees' perception of organizational climate in Shangri-La Hotels and Resorts and its relationship towards employees' turnover intention. The secondary objective of this study is to use the finding to make recommendation to improve the group's retention strategies.